Evidence in Islamic Criminal Law - Jasni bin Sulong; Zaid Alfauza Marpaung; Gifa Nur Syahara; Sabariana Siregar (Jurnal Sahabat ISNU SU, 2024)
Evidence constitutes a fundamental element in the Islamic criminal justice system, serving as the primary basis for establishing criminal liability while safeguarding the rights of the accused. Islamic criminal law upholds the principle of the presumption of innocence, whereby no individual may be convicted without clear, valid, and convincing evidence. This study aims to examine the concept of evidence in Islamic criminal law, identify the recognized forms of admissible evidence, and analyze the mechanisms for their application in criminal proceedings. This research employs a normative legal research method using a library research approach by examining the Qur'an, Hadith, classical and contemporary Islamic legal literature, statutory references, and relevant scholarly publications. The findings indicate that Islamic criminal law recognizes several forms of evidence, including confession (iqrār), testimony (shahādah), oath (yamīn), refusal to take an oath (nukūl), collective oath (qasāmah), the judge’s knowledge ('ilm al-qāḍī), and circumstantial evidence (qarīnah). Each form of evidence possesses specific legal requirements and varying evidentiary value depending on the nature of the criminal offense. The evidentiary process is governed by the principle that the burden of proof rests upon the claimant, while the defendant has the right to deny the allegation through legally recognized means. Particularly in cases involving ḥudūd and qiṣāṣ, Islamic law requires a higher standard of proof to avoid wrongful convictions and ensure justice. The study concludes that the Islamic evidentiary system is designed not only to determine criminal responsibility but also to protect human rights, uphold fairness, and ensure that judicial decisions are based on certainty rather than suspicion.